Pneumococcal 13-valent polysaccharide vaccination (PCV13) response in patients with pulmonary aspergillosis. Issue 2 (28th February 2020) - Aggarwal, Sunil; Kosmidis, Chris; Denning, David
Abstract : Background: Response to pneumococcal 23-valent polysaccharide vaccine (PPV23) is poor in patients with pulmonary aspergillosis, pneumococcal 13-valent polysaccharide vaccine (PCV13) is believed to be more antigenic. Thus practice at the national aspergillosis centre (NAC), Manchester University NHS foundation trust (MFT) is to give PCV13. However, response to PCV13 has not been studied. Methods We conducted a retrospective, observational study of patients with pulmonary aspergillosis at the NAC, MFT. Patients who had non-protective pre-vaccine levels, and received PCV13 between January-2015 and July-2019 with serology available within 3 months after vaccination were included. Serotype-specific pneumococcal IgG antibodies were quantified for 12 pneumococcal serotypes. Non-protective immunity was defined as pre-vaccine level <0.35μg/mL to > 6 out of 12 serotypes. Protective response was defined as level >1.3μg/mL, or an increase in concentration ≥4-fold for at least 9 of 12 serotypes within 3 months. Results: 47 of 144 patients receiving PCV13 had non-protective pre-vaccination levels and repeat serology within 3 months post-vaccination. 52% and 20%, of patients who received 2 and 1 doses (respectively) developed protective immunity; χ2(1)=2.987, p= 0.084. 42.86%, 69.23%, 42.86%, 50%, and 0% of patients with chronic pulmonary aspergillosis (CPA), allergic bronchopulmonary aspergillosis (ABPA), severe asthma with fungal sensitisation, aspergillus bronchitis, and mixed ABPA and CPA developed protective immunity; χ2(4)=6.329, p=0.176. Conclusion: Patients with CPA respond poorly to PCV13 compared to ABPA. Response to two doses of PCV13 is comparable to one dose of PPV-231. Patients with pulmonary aspergillosis should receive two doses of PCV13 rather than one dose.